Possibilities of Applying the Thematic Contents of Environmental Education in Ethical Education in Slovakia - Baďurová, Barbora (Studia Ecologiae et Bioethicae, 2020)
The text deals with the possibilities of the utilisation of cross-curricular themed Environmental education in the school subject, “Ethical education in Slovakia”, especially in lower secondary education. The text partly stems from work on the project APVV-14-0176 “Didactic Means Facilitating the Implementation of Selected Cross-Curricular Topics in the Teaching of Ethical Education at the Second Level of Primary School”, and offers a brief overview on how the topics of ethical education may overlap with environmental education. To achieve this goal, the first part of the text briefly characterises ethical education in Slovakia, and introduces its key figures and principles, as well as the elements of environmental education in ethical education, and a brief summary of the content of the cross-curricular topic, “Environmental Education in the Current National Curriculum” follow. The suggestions for implementation of environmental education in ethical education in Slovakia, form the last part of the paper, where the author also describes some problem areas of the subjects. The author concludes that it is also possible to apply environmental themes in current ethical education; however, it requires some creativity, critical thinking, suitable teaching materials, and competent, dedicated teachers.